Passive backward acquisitions and downstream collusion - Shiva Shekhar; Tim Paul Thomes (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We investigate the effects of passive backward acquisitions in their efficient upstream supplier on downstream firms' ability to collude in a dynamic game of price competition with homogeneous goods. We find that passive backward acquisitions impede downstream collusion. The main driver of our finding is that a passive backward acquisition secures an acquirer from zero continuation profits after a breakdown of collusion. This anti-collusive effect cannot be outweighed by a lower collusive price that is set by the cartel to increase the acquirer's profit from its claim on the upstream margin.
Keywords: D43; L13; L40; L81; 330; Tacit collusion; passive backward acquisitions; Bertrand competition